Planning experiences in historic cities protected by UNESCO - Cruz, Douver dos Santos (Electronic Journal "Fórum Ambiental da Alta Paulista", 2021)
This article arises from the need to clarify the field of heritage preservation and conservation at the beginning of the 21st century, especially in central areas and historic cities. We went through this reflection in the face of the expressive homogenization of places and mischaracterizations of the landscapes produced with artificial interventions aimed at exploratory tourism, which directly reflect on the loss of the identity of urban heritage and, more ambitiously, with the cities-commodity in large cities, through management of urbanism with new contemporary interventions. The process of patrimonialization of historic cities is seen here from two distant angles in time, space, territory, culture and history, but they reflect the same repercussions for the city: scenography and gentrification, as is the case in Brazil, in Pelourinho in the city of Salvador, in 1992, and Portuguese, in the Quarteirão das Cardosas, in Porto, in 2009. With this, we were able to further question and denounce some perversions in architecture, the result of these economic speculations, which see facade renovation works as useful, that rip apart the entire interior of the heritage, neglecting the entire authentic experience of the city and demonstrate the perversions in the community in the face of the gentrification process, where landscape is transformed giving material form to the difference between cultural and economic power. We believe that it is possible to demonstrate in time to society, which is in constant threat of globalization, that heritage needs to be urgently recovered in order to remain on the continuum of life.